PTU-063 High reticulocyte count predicts mortality in patients awaiting liver transplantation. (28th May 2012) - Parker, R; Armstrong, M A; Corbett, C; Rowe, I; Stephenson, B; Houlihan, D; Ferguson, J
Abstract : Introduction: The shortage of donor organs for liver transplantation (LT) makes it essential that organs are allocated to patients with greatest need. There has been increasing interest in haemoglobin as a predictor of LT outcomes. We investigated red cell parameters as predictors of survival after LT assessment. Methods: Data on patients with end-stage liver disease assessed for LT between 2008 and 2010 at University Hospitals Birmingham, UK, were reviewed retrospectively. Kaplan–Meier and Cox regression analysis identified parameters predictive of death on the waiting list. To construct an updated UKELD model including high reticulocyte count (defined as >80), cases that had not received LT at 12 months were randomly divided into two groups (2:1 ratio) to for model building and testing. Accuracy of the existing and new and models was tested by calculation of c-statistics. Results: Data were collected from 393 patients. Median age was 55 years (range 17–73), 60% were male. Median UKELD was 56 (44–76). Median follow-up was 18 (0–45) months. In total 144 (37%) underwent LT. Abnormal reticulocyte count, seen in 120 patients (31%), was greatest predictor of death without LT (HR 3.1; 95% CI 1.7 to 5.6), compared to haemoglobin (HR 2.5; 95% CI 1.3 to 4.5) and MCV (HR 0.6; 95% CI 0.3 to 1.2). Abnormal reticulocyte count remained a significant predictor of death after adjustment for age, gender and diagnosis (p80; yes=1, No=0]). This model had improved predictive accuracy with a c-statistic of 0.79. Conclusion: High reticulocyte count is associated with increased risk of death in patients awaiting LT. Remodelling UKELD to include high reticulocyte count improved accuracy of predicting death on the LT waiting list. Competing interests: None declared.